(untitled) (LACCEI, 2024)
There are Andean tubers, such as yacon (Smallanthus sonchifolius), whose consumption is limited despite the multiple functional properties it possesses preparations made from this tuber are scarce. Previous studies indicate that Andean tubers contain a wide variety of uses that could be implemented in people’s diets. The study carried out was the result of a thesis and its objective was to determine the sensory perception of a sorbet-type ice cream based on yacon (Smallanthus sonchifolius) in the city of Trujillo-Peru, 2023. The study had a quantitative, descriptive, applied and cross. The sample consisted of 123 students from the Gastronomy and Restaurant Management career. The instrument used was an observation guide, which evaluates 4 dimensions: color, smell, taste and texture. Each participant was given a 30 ml sample of sherbet ice cream. After analyzing the data, it was found that the product had a general acceptance of 55%, within the dimensions evaluated, the one with the highest score was the flavor with 83% acceptance, followed by the texture with 81% acceptance, then the color, with an acceptance of 61% and finally the smell had an acceptance of 46%. The participants described the product as: sweet, refreshing, fruity, odorless, yellow in color and natural looking. It was concluded that the yacon (Smallanthus sonchifolius)-based ice cream sorbet had a sensory perception of "pleasant" so it can be turned into a product with functional properties with commercial potential. Further studies are recommended to improve the standard formulation in relation to smell and determination of sensory perception in other participating groups.